A Case of Worsening Deep Cerebral Venous Sinus Thrombosis Managed by Intrasinus Thrombolysis. (12th October 2011) - Sood, Nidhi; Sood, Nikhil; Talkad, Arun
Abstract : Cerebral venous sinus thrombosis (CVST) is an uncommon condition with severe consequences. Although we do not know the exact incidence and prevalence of CVST, it is an important diagnosis. Over the past decade, it has been diagnosed more frequently due to greater awareness and availability of noninvasive diagnostic techniques. Furthermore, routine diagnostic neuroimaging has been used to monitor the clinical progress of these patients, especially in deteriorating cases. In order to decrease morbidity and mortality, an understanding of CVST treatment options is important. Treatment of extensive intracranial venous sinus thrombosis with intrasinus infusion of recombinant tissue plasminogen activator (rt-PA) is relatively controversial as there are no clear guidelines in regards to appropriate therapeutic management. We report a case of successful intrasinus thrombolysis of deep cerebral sinus thrombosis (DCST) resulting in rapid radiographic improvement associated with complete clinical recovery.